Concentrating solar power (CSP) assisted FO hybrid systems for desalination of seawater: a preliminary study - Ahmed, Sultan; Alghamdi, Ahmed S.; Mahmoud, Amr Mohamed; Albutuwaybh, Hajer H.; Almadeh, Jenan A. (Frontiers in Water, 2025)
This study examines the feasibility and economic performance of Forward Osmosis (FO) desalination systems powered by Concentrated Solar Power (CSP) technologies, specifically Parabolic Trough (PT) and Linear Fresnel Reflector (LFR) systems. The study evaluates two operational scenarios: batch-mode operation without Thermal Energy Storage (TES) and continuous operation with TES. Seawater serves as the Feed Solution (FS), while Dimethyl Ether (DME) is used as the Draw Solution (DS), recovered through a thermal separation process powered by CSP. Key performance metrics analysed include the Capacity Factor (CF), Levelized Cost of Thermal Energy (LCoT), and Levelized Cost of Water (LCoW). Results indicate that in the non-TES scenario, where the FO system operates for 8 h per day, the PT system achieves the lowest LCoW, ranging between $0.74/m3 and $1.91/m3, while the LFR system exhibits slightly higher costs at $0.89/m3 to $2.38/m3. However, this batch-mode operation limits system efficiency and results in excess unused solar energy due to defocusing. In contrast, the TES scenario enables 24-h continuous operation, significantly increasing CF to 99.73% for LFR but also raising costs. The LCoW for LFR in this configuration ranges from $1.69/m3 to $3.48/m3, with the high cost of TES driving up LCoT between 7.72 and 11.60 c$/kWhth. The findings highlight a fundamental trade-off: while TES enhances operational stability, it introduces prohibitive storage costs, making batch-mode CSP-FO configurations more economically viable. FO module costs significantly impact LCoW, with thermal energy OPEX dominating cost composition in TES cases, while FO CAPEX becomes more influential at higher module prices. Additionally, lower solar field output temperatures reduce LCoW in non-TES scenarios, whereas in TES cases, storage costs remain the primary determinant of economic performance. This study contributes to the growing body of research on sustainable desalination by critically assessing CSP-FO integration under real-world constraints. Compared to conventional RO or MED systems, CSP-FO presents a viable alternative in regions where direct solar-driven desalination is preferred. Future research should prioritize reducing TES costs through alternative storage materials, exploring hybrid CSP-PV-FO configurations, and enhancing FO membrane efficiency to improve overall system feasibility and scalability in arid regions.